2015
DOI: 10.1002/cmdc.201500502
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Bioconjugates in Cancer Detection and Therapy

Abstract: Nucleoside- and nucleotide-based chemotherapeutics have been used to treat cancer for more than 50 years. However, their inherent cytotoxicities and the emergent resistance of tumors against treatment has inspired a new wave of compounds in which the overall pharmacological profile of the bioactive nucleic acid component is improved by conjugation with delivery vectors, small-molecule drugs, and/or imaging modalities. In this manner, nucleic acid bioconjugates have the potential for targeting and effecting mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…Azide-modified nucleoside triphosphates have been shown to be incorporated into the DNA backbone providing bioorthogonal handles for further label-ing. 84,85 Alkenyl deoxynucleosides and alkynylnucleosides have been employed to label rat DNA and RNA. 82 Huang et al reported using 5-vinyl-2′-deoxyuridine as a bioorthogonal precursor for labeling viral genomes.…”
Section: Incorporation Of Bioorthogonal Handlesmentioning
confidence: 99%
“…Azide-modified nucleoside triphosphates have been shown to be incorporated into the DNA backbone providing bioorthogonal handles for further label-ing. 84,85 Alkenyl deoxynucleosides and alkynylnucleosides have been employed to label rat DNA and RNA. 82 Huang et al reported using 5-vinyl-2′-deoxyuridine as a bioorthogonal precursor for labeling viral genomes.…”
Section: Incorporation Of Bioorthogonal Handlesmentioning
confidence: 99%
“…remain bound within the target cell) (Fig. 2), [14,25,29,30] conjugation chemistry has a major role to play in the development of efficient peptide-oligonucleotide conjugates. This review focuses specifically on the various chemical approaches used to form oligonucleotide and peptide conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…Among those, the use as probes for in situ hybridization, in microarrays, for some PCR applications, or the tracking of oligonucleotides in vitro or in vivo requires attachment of fluorescent or other labels to chemically synthesized oligonucleotides [5]. In addition, bioconjugation of various ligands has an important role in the development of therapeutically active oligonucleotide agents [6,7]. The tethering of proteins, peptides or small molecule receptor ligands for targeting applications may be instrumental for overcoming the inherent, yet not sufficiently solved issues of pharmaceutical development.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach is limited to hepatocyte targeting and thus directed to liver diseases, and other targeting moieties seem to be needed for expanding the target space of oligonucleotide therapeutics. Besides conferring receptor-targeting properties, the attachment of certain ligands to oligonucleotides may also influence pharmacokinetics and biodistribution in a nonspecific way, by increasing the molecular weight [12][13][14] or by modulating lipophilicity [7] or plasma protein binding. In addition, cellular uptake and endosomal escape are aimed to be increased by attaching cationic small molecules or peptides [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%